A weighted stochastic restricted ridge estimator in partially linear model. Issue 18 (17th September 2017) - Wu, Jibo; Asar, Yasin
ABSTRACT: In this article, we consider the estimation of a partially linear model when stochastic linear restrictions on the parameter components are assumed to hold. Based on the weighted mixed estimator, profile least-squares method, and ridge method, a weighted stochastic restricted ridge estimator of the parametric component is introduced. The properties of the new estimator are also discussed. Finally, a simulation study is given to show the performance of the new estimator.